Adolescent desires. Between teen dramas, online pornography and sexual fluidity - Burgio, Giuseppe (Encyclopaideia, 2021)
Through the analysis of the contents of the most recent and popular teen dramas, of the diffusion of online pornography and of data from surveys on adolescent sexuality, we hypothesise how today's adolescents live an increasingly carefree sexual behaviour with respect to the choice of sexual objects, more free from ethical and social norms, in a completely changed relationship with an adult world no longer seen as a more or less controversial reference point. This panorama urges us to renew the theoretical lenses through which we look at an adolescence that is completely different from previous ones with regard to its relationship with sexuality.